Nitric oxide in the field: Prevalence and use of nitrates by dietitians and nutritionists in spanish elite soccer - Sebastiá-Rico, J.; Cabeza-Melendre, D.; Anderson, L.; Martínez-Sanz, J. M. (Nutrients, 2023)
Soccer players make frequent use of dietary supplements to improve performance. One of the most widely used strategies to optimize performance is to increase the bioavailability of nitric oxide through nitrates, as it could delay fatigue during physical exertion, among other benefits. This may be positive for performance in soccer, although there is almost no research in professional soccer. The aim of the study was to evaluate the use of nitrates and behaviours related to their consumption in Spanish elite soccer clubs. Dietitian-nutritionist representatives from 45 teams from the most important Spanish soccer leagues completed an online survey to determine if, when, how and why nitrates are prescribed to soccer players. Of the total sample, 55.6% indicated providing nitrates, always before matches, but only 36% in training. There was a wide variation and lack of consistency in the timing, dosage and form of administration of nitrates. The use of mouthwashes or the protocol of chronic nitrate intake was not taken into account in most cases. The present study indicates a lack of interpretation between scientific knowledge and its application in practice, highlighting the need for future research to better understand how to optimize the use of nitrates in professional soccer.